The making sense of politics, media, and law : rhetorical performance as invention, creation, production - Watt, Gary (Cambridge : Cambridge University Press, 2023)
From Trump's 'make America great again' to Johnson's 'build back better', performative politicians use The Making Sense to persuade their public audiences. Law 'makers' do it too: A courtroom trial is a 'truth factory' in which facts are not found but forged. The 'court of popular opinion' is another such factory, though its processes are often flawed and its products faulty. Where courts of law aim to make civil peace, 'trial by Twitter' makes civil strife. Even in 'mainstream' media, journalists make news for public consumption, so that all news is to an extent 'fake news'. In a world of making, how can we separate craft from craftiness? With insights from disciplines including law, politics, rhetoric, media studies, psychology, sociology, marketing, and performance studies, The Making Sense of Politics, Media, and Law offers a constructive way to approach controversies from transgender identity to cancel culture. This title is also available as open access on Cambridge Core.
The Making Sense : Introduction -- Invention, Creation, Production Invention, Creation, Production Invention, Creation, Production -- Artefaction : Making Things -- The Truth Factory : Crafting Fact and Law -- Making Sex Change : Legal Engendering of Trans People -- Making Faces, Performing Persons -- The Acting President -- Political Confection : Making a Meal of It -- State Building -- Co-Production and Populism Production -- Faking News -- Making Mistakes -- Trial by Twitter and Cancel Culture.
Title from publisher's bibliographic system (viewed on 06 Apr 2023).
Keywords: Sociological jurisprudence; Mass media -- Law and legislation -- Social aspects; Rhetoric -- Social aspects